Islamic Spectrum in Java: By Timothy Daniels (Surrey, UK: Ashgate, 2009. hbk. 210 pages) (American Journal of Islam and Society, 2011)
Timothy Daniels’ Islamic Spectrum in Java critically examines the myriadof ways in which Javanese Muslims draw on religious and secular ideas toproject desirable futures for their local societies, for the Indonesian nation,and for Indonesia’s place in the global economic, political, and culturalstructures of the twenty-first century. This book identifies a broad rangeof desirable futures projected by Javanese Muslims, as well as a range ofbeliefs and practices that comprise Javanese Islam (12). While this engagingwork is very likely to appeal to scholars in many fields, theoreticallyand methodologically it is foremost an anthropological study. Synthesizingsymbolic and cognitive anthropology in order to “provide ‘thick description’1 of polysemous symbols . . . and to ascertain the social distributionof knowledge and formation of mental representations in various contexts(4),” Daniels draws primarily on ethnographic fieldwork conducted in theYogyakarta area of south-central Java from 2003 to 2004.Daniels makes a complex argument, focusing on issues of globalization,localization, social change, identity formation, and the place of Islamin Javanese culture. He contends that in projecting a range of desirable futures,Javanese Muslims are able to negotiate globalization and directionsof social change on their own terms by drawing from local culture andtheir interpretations of Islam in different ways. In particular, he examinesto what extent particular ideological positions expressed by Javanese Muslimscontribute to or undermine processes of equalization—“processes ofweakening, undermining, and lessening hierarchical formations” (8). Insupporting his argument, he addresses other related issues as well, includingconcepts of spiritual power, gender, sexuality, and class ...